Explaining Stress and Depression Level of Nurses: The Effects of Role Conflict and Role Ambiguity - Kapusuz, Ayşe Gökçen (International Journal of Management and Sustainability, 2019)
Productive human resources and behaviors play a significant role in the task and performance-oriented organizations in today’s competitive, innovative, developable, and profitable business life. In this ever-changing and increasingly globalized World, people confront stress and right after depression based on their different roles, threats and events. The aim of this research is to analyze the effects of role conflict and role ambiguity of nurses upon the stress and depression with different theoretical backgrounds. In this study, the relationship among all mentioned variables was examined and analyzed based on the survey data with the participation of 141 randomly chosen nurses from the public hospital in Osmaniye, Turkey. Based on the results of hierarchical regression analysis; role ambiguity, role conflict, and depression are significantly related to job stress of nurses. Besides, there is an insignificant relationship between role conflict and depression. On the other hand, there are negative effects of role ambiguity upon the depression of nurses. This negative relationship between role ambiguity and depression increases from -0.309 to -0.321 when combined with role conflict. Role conflict and role ambiguities are two factors that cause to stress and depression in both personal and work life. The productivity of workers/employees especially in the health sector is depending on different environmental, individual, and psychological factors. Managers should consider the changing of the work environment and variability of patients besides personal needs and abilities while distributing the extra roles of nurses.